Chronic fatigue syndrome related to herpes simplex viruses infection – a narrative review - Bieńkowski, Kuba; Bielaska, Albert; Wesołek-Bielaska, Ewelina; Kołodziej, Wojciech; Gałązka, Jakub Krzysztof; Greszta, Magdalena (Quality in Sport, 2024)
This article reviews the potential impact of herpes simplex viruses (HSV) on chronic fatigue syndrome (CFS). HSV-1 and HSV-2 are prevalent pathogens, with HSV-1 acquired early in life and HSV-2 typically transmitted sexually. Studies have shown an association between HSV and CFS, with HSV-1 detected in saliva and cerebrospinal fluid of CFS patients and elevated HSV-2 antibodies found in CFS patients. Immunological abnormalities, including increased pro-inflammatory cytokines and chemokines, suggest immune dysregulation in CFS patients infected with HSV. HSV infections can also disrupt the hypothalamic-pituitary-adrenal axis and autonomic nervous system, impacting energy metabolism regulation and contributing to CFS fatigue. Neuroinflammation, indicated by increased translocator protein binding in CFS patients' brains, may play a role in CFS symptoms. However, the mechanisms linking HSV to CFS and the contribution of viral-induced neuroinflammation are still unclear. Despite the evidence, understanding the complex interactions between HSV, immune responses, and other factors in CFS remains challenging. In conclusion, HSV, particularly HSV-1 and HSV-2, may contribute to CFS development. Further research is needed to unravel the mechanisms involved and identify potential therapeutic interventions.